Post‐9/11 military veterans' adjustment to civilian life over time following separation from service. Issue 9 (19th April 2021) - Park, Crystal L.; Sacco, Shane J.; Finkelstein‐Fox, Lucy; Sinnott, Sinead M.; Scoglio, Arielle A. J.; Lee, Sharon Y.; Gnall, Katherine E.; Mazure, Carolyn; Shirk, Steven D.; Hoff, Rani A.; Kraus, Shane W.
Abstract: Objectives: US military veterans face many challenges in transitioning to civilian life; little information is available regarding veterans' reintegration experiences over time. The current study characterized veterans' postdeployment stressful life events and concurrent psychosocial wellbeing over one year and determined how stressors and wellbeing differ by demographic factors. Methods: Recent Post‐911 veterans ( n  = 402) were assessed approximately every three months for 1 year. Participants were 60% men, primarily White (78%), and 12% Latinx; the average age was 36 years. Results: The frequency of stressful events decreased over time but was higher for men and minority‐race veterans (independent of time since separation). Veterans reported high mean levels of posttraumatic stress disorder, anxiety, and insomnia symptoms, which improved slightly over time. Minority‐race and Latinx veterans had higher symptom levels and slower rates of symptom reduction. Conclusion: Veterans remain distressed in their overall transition to civilian life. Interventions to promote resilience and help veterans manage readjustment to civilian life appear urgently needed.